Yield and quality of soybean seeds as affected by growing conditions - Đukić Vojin; Balešević-Tubić Svetlana; Đorđević Vuk; Tatić Mladen; Dozet Gordana; Jaćimović Goran; Petrović Kristina (Ratarstvo i Povrtarstvo, 2011)
Effect of environmental conditions (temperatures and precipitation) on soybean yield and seed quality was examined during two years. Trials with four replications were located at experimental fields of Institute of Field and Vegetable Crops at Rimski Šančevi. Environmental conditions had significant influence on examined traits, and higher yield and seed quality was achieved during beneficial year. There was a moderate positive relationship between yield and seed germination.